Implementation of an Online Shoe Store Website to Improve the Shoe Sales Process - Sharil Ramadani; Sandy Kosasi (STMIK Pontianak, 2021)
The purpose of this community development is to design a sales website that can be used as a place for product management in the form of store and product information in stores that can be accessed through the store website, product purchase transactions and can facilitate the store in the process of purchasing products at the store. The form of research used is a case study with the Design Science Research method. HTML and PHP programming language with MySQL database in phpMyAdmin and using Laravel Framework with Model View Controller concept. Coding editing application used by Visual Studio Code, with XAMPP as the local server. The modeling software used is Unifield Modeling Language (UML). The software design method used is the Extreme Programming method. Testing is carried out using the Black-Box Testing method, the Equivalence partitioning technique is carried out in stages starting from unit testing, integration testing,system testing and acceptance testing. This research produces a Sales Website that functions to manage the service process to consumers in the form of store information and store products.